EFEKTIVITAS MANAJEMEN HOTEL SYARIAH : STUDI KASUS KEPATUHAN SYARIAH DI PROVINSI RIAU - Saib, Khaidir; Yoseanti, Tari (Eko dan Bisnis: Riau Economic and Business Review, 2022)
in some hospitality businesses, efforts to increase hotel revenue, some hotels ignore visitor requirements. Many hotels allow unmarried couples to stay. No wonder many people say that the hotel is a place of immorality, gambling, alcohol and drugs. In this case, it provides opportunities for sharia entrepreneurs to build sharia-based hotels. Not only to change the bad image of hotels, sharia-based hotels have a mission to change people's mindsets and create social order in society. With an increase in sharia-based hotel investment, it is hoped that it can improve the moral quality of religious people and uphold the noble culture of the Riau people. Methodology This study uses a qualitative method. Qualitative research is research that is used to study the state of natural objects, where the researcher is the main instrument. The purpose of qualitative research is to describe a phenomenon as deeply as possible by collecting the deepest data, which shows the importance of depth and detail of the data studied. The conclusion of this study is that sharia compliance in sharia hotel management in Riau Province is quite good, especially from the aspect of service ethics in accordance with sharia principles. Hotels with sharia nuances that are used in the management, services and facilities provided can be an attraction for potential consumers or Muslim tourists